Change Management Perception and Employees' Perception of Wellbeing in the Ghana Revenue Authority - Mensah, G.K. (University of Ghana, 2013)
The changing nature of work these days has brought about issues of psychological wellbeing of employees affected by organizational restructuring. In this regard, the present study investigated the mediating effects of pay satisfaction and employability on the relationship between perceived change management and employee wellbeing among some 274 employ ees of a recently integrated/merged revenue agencies into the Ghana Revenue Authority (GRA). A multi-stage quota and convenience sampling techniques were employed to collect cross-sectional data from employees. Independent t-test, Multiple Regression and Mediation Analyses were conducted on the data. Results indicated that employees who perceived change management to be positive had better wellbeing than those who perceived it to be negative with pay satisfaction mediating. This implied that the effect of perceived change management on employee wellbeing is significantly dependent on the level of satisfaction employees have with their current pay. The mediating role of perceived employability was not significant. Results are discussed with reference to the frameworks of individual perceptions of events and latent deprivation theories that seek to explain why individuals show lowered wellbeing when their welfare is compromised during the process of organizational change management.
Thesis (MPHIL)-University of Ghana, 2013